Epilepsy Following Neonatal Seizures Secondary to Hemorrhagic Stroke in Term Neonates. (April 2016) - Venkatesan, Charu; Millichap, John J.; Krueger, Jena M.; Nangia, Srishti; Ritacco, David G.; Stack, Cynthia; Nordli, Douglas R.
Intracranial hemorrhage accounts for about 50% of all pediatric stroke. Studies of term infants with intracranial hemorrhage have shown favorable motor and cognitive outcome. The goal of this study was to examine the risk of developing epilepsy in full-term infants with intracranial hemorrhage. A retrospective study was performed of term neonates (greater than or equal to 37 weeks gestation) with intracranial hemorrhage and confirmed seizures. Fifteen patients with intracranial hemorrhage and neonatal seizures were identified. Four patients did not have follow-up information beyond the neonatal period (1 death, 3 lost to follow-up after initial clinic visit). The average follow-up period for the remaining 11 patients was approximately 22 months. Ten out of the 11 patients (91%) who were followed were seizure-free and off antiepileptic medications. One patient required a ventriculoperitoneal shunt and subsequently developed infantile spasms. The authors found that overall outcome was favorable with respect to development of epilepsy.